What is Market: Socio-Economic Approach - Radaev, Vadim (Journal of Economic Sociology, 2010)
The end. The beginning see in 2006. Т. 7. № 5. The second part of the paper is devoted to the analysis of the assumptions of socio-economic and marketing approaches. The author formulates and supports the principle of methodological pluralism in contemporary market studies.